Amyloid deposition in bilateral mandibular condyles and buccal mucosa. Issue 6 (November 2016) - Nakano, Takafumi; Jinbu, Yoshinori; Okada, Naruo; Sase, Miwako; Hayasaka, Junichi; Tsuchiya, Yoshiyuki; Itoh, Hiroto; Noguchi, Tadahide; Hoshi, Kentaro; Mori, Yoshiyuki
Abstract: We report a very rare case of systemic amyloidosis occurring in bilateral mandibular condyles and showing condylar bone destruction and lesions in the buccal mucosa bilaterally. The patient was a 61-year-old man complaining of malocclusion in which the lower teeth extended abnormally over the upper teeth. He first noticed this about 1 year earlier. Medical history included renal cancer, rheumatic myalgia in multiple joints, osteoporosis, hypothyroidism, chronic hepatitis, malignant lymphoma and hemodialysis for renal failure. Panoramic radiography and computed tomography showed bone destruction in bilateral mandibular condyles and a soft tissue mass lesion around the condyle. Slightly raised mass lesions with areas of whitish and purplish coloration were also observed on the buccal mucosa bilaterally. Histopathological examination revealed amyloid deposition in these lesions, and AA and/or Aβ2M amyloidosis was diagnosed. However, we were informed that the patient died within 3 months from when he had a last check-up at our clinic due to systemic problems.